Interfacial self-assembled behavior of pH/light-responsive host-guest alginate-based supra-amphiphiles for controlling emulsifying property. (15th August 2021) - Yang, Shujuan; Qin, Wenqi; Zhao, Xinyu; He, Furui; Gong, Houkui; Liu, Yuanyuan; Feng, Yuhong; Zhou, Yang; Yu, Gaobo; Li, Jiacheng
Abstract: Soft emulsifiers with relatively suitable structural controllability are necessarily required for the preparation of multifunctional Pickering emulsions. Herein, a β-cyclodextrin-grafted alginate/azobenzene-functionalized dodecyl (Alg-β-CD/AzoC. 12) polymeric supra-amphiphile was designed based on the host-guest interfacial self-assembly. As compared with Alg-β-CD amphiphilic polymers, the interfacial tension of Alg-β-CD/AzoC12 supra-amphiphilic assemblies reduced from 29.57 mN/m to 0.18 mN/m, indicating the great amphiphilicity derived from Alg-β-CD/AzoC12 supra-amphiphilic assemblies. With the increase of pH, the interfacial microstructures transformed from flocculated structures, spherical structures into deformed structures. Especially, the spherical microstructures with the highest interfacial viscoelasticity and thickness demonstrated the highest emulsifying efficiency due to the steric hindrance mechanism. Moreover, the interfacial elastic modulus of adsorbed layers exhibited ~4 times of that upon the ultraviolet illumination. These results disclosed that the interfacial microstructures could be readily regulated by the tunable amphiphilicity of Alg-β-CD/AzoC12 assemblies, which would be useful for the applications of Pickering emulsions in numerous fields. Highlights: Supra-amphiphilic assemblies showed relatively more matched amphiphilicity. Polymeric alginate moieties increased host-guest interfacial adsorption. Polymeric host-guest assemblies formed a thicker interfacial film with higher viscoelasticity. Polymeric supra-amphiphile showed better interfacial structural controllability.